An interdisciplinary review to develop guidelines for modeling population displacement as a function of infrastructure reconstruction decisions. (December 2019) - Rand, Krista; Fleming, Cody H.
Abstract: Multiyear population displacement is a feature of natural disasters that have caused widespread infrastructure damage. This interdisciplinary, transportation-centric survey paper offers guidelines for civil infrastructure system (CIS) models supporting recovery managers and transportation system managers who are seeking to reduce displacement duration. Social science and transportation literature describe the linkages between infrastructure and long-term population displacement and identify key infrastructure systems needed to resolve population displacement. Resilience literature, particularly the well-known performance recovery curve, is extended to show how infrastructure interdependencies affect reconstruction timelines, and how repair of key infrastructure therefore forms a lower bound on displacement duration that can be estimated using a CIS. CIS modeling literature describes model types and interdependencies for post-disaster recovery models concerned with displacement. These high-level requirements and design specifications are summarized within a simple scorecard and used to evaluate thirteen recent quantitative, recovery-focused CIS models for potential application to disaster displacement. The most common data gaps are transportation and building systems, and a majority of models neglect jurisdictions, funding constraints, and any mention of people in model goals or outputs. We conclude by identifying urgent research questions, discussing issues of data type and resolution, and suggesting appropriate outputs for decision support. Highlights: Social science and transport literature connect reconstruction and displacement. Transportation and five other infrastructure systems underlie displacement modeling. Interdependencies can be used to estimate lower bounds of displacement duration. Recovery models analyzing interdependencies after widespread damage exist. Future work cannot neglect transport, buildings, jurisdictions, funding, or people.